2015
DOI: 10.1158/1078-0432.ccr-14-3090
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Dose-Escalation Study of Antibody BI-505 in Relapsed/Refractory Multiple Myeloma

Abstract: Purpose: This multicenter, first-in-human study evaluated safety, tolerability, pharmacokinetics, and pharmacodynamics of BI-505, a human anti-ICAM-1 monoclonal antibody, in advanced relapsed/refractory multiple myeloma patients.Experimental Design: BI-505 was given intravenously, every 2 weeks, at escalating doses from 0.0004 to 20 mg/kg, with extension of therapy until disease progression for responding or stable patients receiving 0.09 mg/kg or higher doses.Results: A total of 35 patients were enrolled. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…A phase 1 dose-escalation study with BI-505 is completed, and it is ready for entering the next phase of clinical trials (49) (Table 5). Thalidomide and its analogue lenalidomide are immunomodulators that function as anti-TNFα agents, via the regulation of cell surface expression of key adhesion molecules like ICAM-1, VCAM-1, E-selectin and L-selectin thereby decreasing cell-cell interaction between T-ALL cells and umbilical vein endothelial cells (50,51).…”
Section: Cams Involved In Chemoprotection In Allmentioning
confidence: 99%
“…A phase 1 dose-escalation study with BI-505 is completed, and it is ready for entering the next phase of clinical trials (49) (Table 5). Thalidomide and its analogue lenalidomide are immunomodulators that function as anti-TNFα agents, via the regulation of cell surface expression of key adhesion molecules like ICAM-1, VCAM-1, E-selectin and L-selectin thereby decreasing cell-cell interaction between T-ALL cells and umbilical vein endothelial cells (50,51).…”
Section: Cams Involved In Chemoprotection In Allmentioning
confidence: 99%
“…[3][4][5][6][7] Other mAbs directed against MM cellular antigens that have demonstrated at least stable disease include those directed against CD138 (BT062), CD54/ICAM-1 (BI-505), and CD74 (milatuzumab). [8][9][10] The development of therapeutic mAbs for the treatment of MM has also been directed against growth factors and their receptors (eg, interleukin-6, interleukin-6 receptor, insulin-like growth factor-1 or -2, vascular endothelial growth factor, and B-cell activating factor). Antibodies that augment the host immune response through immune checkpoint inhibitors targeting programmed cell death protein 1 (PD-1) and PD ligand 1 (PD-L1) are also in development.…”
Section: Targets For Monoclonal Antibody (Mab) Therapymentioning
confidence: 99%
“…Increased ICAM-1 expression levels have been observed in multiple myeloma (15) and across many disparate carcinomas including breast (16), pancreas (17), and gastric (18) tumors, and are correlated with tumor progression and metastatic capability (19). Moreover, clinical trials support the safety and tolerability of targeting ICAM-1 using monoclonal antibodies (20–24). Previous studies have shown that ICAM-1 expression is highly correlated with both the malignancy and metastatic status of thyroid tumors, as well as the V600E BRAF (BRAF V600E ) mutation (25, 26).…”
Section: Introductionmentioning
confidence: 97%